Pengaruh Eduksi Perawatan Bayi Berat Badan Lahir Rendah (BBLR) Terhadap Tingkat Kecemasan Ibu Bayi di Ruang Perinatologi RSUD Karawang - Saryati, Saryati; Risdiana, Rani (Universitas Malahayati, 2025)
ABSTRACT Low Birth Weight (LBW) babies are babies whose birth weight is less than 2,500 grams. This condition occurs more often in twins or babies born prematurely. Babies with low birth weight (LBW) can have a severe impact on their growth and development. They are at greater risk of death, stunting and lower IQ than full-term babies. Babies with low birth weight require special care because they can cause various health problems due to unstable conditions. The impact of this condition will trigger anxiety for mothers who have babies with low birth weight which can be influenced by the mother's age, education and the number of children she has given birth to. Factors that influence the concerns of mothers who have low birth weight (LBW) babies include the mother's lack of knowledge about the condition and care given to her child, the atmosphere of the baby care room, the appearance of the baby and role conflict because the mother cannot interact with her baby intensely. One effort to increase the mother's knowledge of the baby in order to reduce the anxiety they feel is by providing education. To determine the effect of LBW care education on the anxiety level of mothers who have LBW babies in the Perinatology room at Karawang Regional Hospital. The type of research used is quantitative research with Pre-Experimental research methods using One Group Pretest-Posttest Design. The instrument used was a pre- and post-education questionnaire using the Hamilton Anxiety Rating Scale (HARS) anxiety scale. The sampling technique used in this research is Non Probability Sampling with an Incidental Sampling approach. The data collection tool uses a questionnaire sheet and data analysis uses the Paired Sample T-Test. There is an influence of providing education on caring for LBW babies on the anxiety level of mothers who have LBW babies in the Perinatology room at Karawang District Hospital with a p-value of 0.030. From the results of research that has been carried out, it is known that there is a significant effect of providing education on the anxiety level of mothers who have LBW babies in the Perinatology Room at Karawang Regional Hospital. It is known that there is a difference between the anxiety level of the baby's mother before and after being given the educational intervention. Keywords: LBW, Anxiety and Health Education. ABSTRAK Bayi Berat Lahir Rendah (BBLR) adalah bayi yang berat lahirnya kurang dari 2.500 gram. Kondisi ini lebih sering terjadi pada bayi kembar atau bayi yang lahir secara prematur. Bayi dengan berat lahir rendah (BBLR) dapat memberikan dampak yang parah terhadap tumbuh kembangnya. Mereka berisiko lebih besar mengalami kematian, stunting, dan IQ lebih rendah dibandingkan bayi cukup bulan. Bayi dengan berat badan lahir rendah memerlukan perawatan khusus karena dapat menimbulkan berbagai gangguan kesehatan akibat kondisi yang tidak stabil. Dampak dari kondisi tersebut akan memicu kecemasan ibu yang memiliki bayi dengan berat badan rendah yang dapat dipengaruhi oleh usia ibu, pendidikan, dan jumlah anak yang pernah dilahirkannya. Faktor yang mempengaruhi kekhawatiran ibu yang mempunyai bayi berat lahir rendah (BBLR) antara lain adalah kurangnya pengetahuan ibu tentang kondisi dan perawatan yang diberikan kepada anaknya, suasana ruang perawatan bayi, penampilan dari buah hati dan konflik peran karena ibu tidak dapat berinteraksi dengan bayinya secara intens. Salah satu upaya untuk meningkatkan pengetahuan ibu bayi agar dapat mengurangi kecemasan yang dirasakan adalah dengan memberikan edukasi. Untuk mengetahui pengaruh edukasi perawatan BBLR terhadap tingkat kecemasan ibu yang memiliki bayi BBLR di ruang Perinatologi RSUD Karawang. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan metode penelitian Pre-Eksperimental menggunakan One Group Pretest-Posttest Design. Instrumen yang digunakan adalah kuesioner pre dan post edukasi menggunakan skala kecemasan Hamilton Anxiety Rating Scale (HARS). Teknik sampling yang digunakan dalam penelitian ini yaitu Non Probability Sampling dengan pendekatan Insidental Sampling. Alat pengumpulan data menggunakan lembar kuesioner dan analisa data menggunakan Uji Paired Sample T-Test. adanya pengaruh pemberian edukasi perawatan bayi BBLR terhadap tingkat kecemasan ibu yang memiliki bayi BBLR di ruang Perinatologi RSUD Karawang dengan nilai p-value 0,030. Dari hasil penelitian yang telah dilaksanakan diketahuiadanya pengaruh yang bermakna dari pemberian edukasi terhadap tingkat kecemasan ibu yang memiliki bayi BBLR di Ruang Perinatologi RSUD Karawang. Diketahui bahwa ada perbedaan antara tingkat kecemasan ibu bayi sebelum dan sesudah diberikan intervensi pemberian edukasi. Kata Kunci: BBLR, Kecemasan dan Edukasi Kesehatan